Persusadaan Otomobil Kedua Sdn Bhd - Laura Angelica Gutierrez Posada; Altaf AlDhafiri; Hajar Al Shalahi; Abdaluziz Alshowaier (AIBPM Publisher, 2019)
In Malaysia, automotive trade is rapid growing industry. It is considered as the one of most important manufacturing industry sectors. Automotive industry is considered as the one of the crucial industries by the Malaysia government. According to the government representor, the rapid growth in the manufacturing of the automotive leads the country to be developed nation by the end of 2020 (Arshad, 2001). According to Malaysia Automotive Institute (MAI) Chief Datuk Madani Sahari automotive sector is going to contribute in the GDP of Malaysia about 10% of the total by the end of 2020. In Malaysia economy the automotive Perodua Company is also contributing a lot in the automotive sector. The Perodua is playing an important role in the manufacturing, assembling, and service sectors. As the Perodua director was crowned with the title of automotive man of the 2017 year, because of his visionary action and leadership in making the national automaker. Therefore, companies like Perodua are the proud for the Malaysia like developing country which are independent in their automotive manufacturing, engineering and designs. In the presence of the given challenges the automotive industry is facing the issues of increased competition, on the global and national level. Therefore, Perodua has to make the strategic direction and also gave the basic framework by reviewing the current status of automotive sector. Therefore, Perodua will have the battle on national and national level. The new designs of Perodua are having new technology and quality. The quality and productivity of Perodua is the mission of the company which enhance the sustainability of the active vendors of Perodua services. Perodua is also known as the world’s best automobile company because of its professionalism, efficiency, quality and reliability of the automobiles. The strategies of the company include the optimizing benefits for the stakeholder and for the customer services, have the social responsibility for the community and environment. This company is unique in its products which attract the customs (Zahari, Halim, Baniamin&Salleh, 2016).